If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(5x + 2) = 3 Reorder the terms: x(2 + 5x) = 3 (2 * x + 5x * x) = 3 (2x + 5x2) = 3 Solving 2x + 5x2 = 3 Solving for variable 'x'. Reorder the terms: -3 + 2x + 5x2 = 3 + -3 Combine like terms: 3 + -3 = 0 -3 + 2x + 5x2 = 0 Factor a trinomial. (-1 + -1x)(3 + -5x) = 0Subproblem 1
Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1Subproblem 2
Set the factor '(3 + -5x)' equal to zero and attempt to solve: Simplifying 3 + -5x = 0 Solving 3 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -5x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -5x = 0 + -3 -5x = 0 + -3 Combine like terms: 0 + -3 = -3 -5x = -3 Divide each side by '-5'. x = 0.6 Simplifying x = 0.6Solution
x = {-1, 0.6}
| 2f-20=4f+10 | | 0.3x-9=1.1x-21 | | 20p-80=-210 | | b^2-2b-15=0 | | -90=30x | | 8x-26=-6+3x | | 1=8(a+8)+1 | | 48=-8a | | x^2+30=13x | | 219-4x=32x+23 | | 7x+6(5x-15)=169 | | -14+13x=5 | | x^2-12x+36=40 | | 4x-3-8x+1=-5x+9 | | 3b+4.4=6.2-3c | | 7w-6w+1=10-4 | | 10h+25=3h-3 | | -(5+6x)=13 | | 4x^2-80x=0 | | -21-11x=15 | | .25(20+4s)-.5(12+2s)= | | x^2+18x+81=50 | | -111-9x=10x+22 | | 3x^3+9x^2+4x+12=0 | | 2x+3x+11=101 | | (r-2t)(r+4w)= | | 5b-2(3b+1)=1 | | 4x-12=60 | | 0.11x+0.8(x-4)=0.01(2x-1) | | Mx+2a=.333(c-x) | | x^2+2x+1=42 | | x^2+12x+36=-25 |